Determination of a “Specific Population Who Could Benefit From Rosuvastatin”: A Secondary Analysis of a Randomized Controlled Trial to Uncover the Novel Value of Rosuvastatin for the Precise Treatment of ARDS - Zhang, Shi; Lu, Zhonghua; Wu, Zongsheng; Xie, Jianfeng; Yang, Yi; Qiu, Haibo (Frontiers in Medicine, 2020)
Background The high heterogeneity of acute respiratory distress syndrome (ARDS) contributes to paradoxical conclusions from previous investigations of rosuvastatin for ARDS. Identification of the population (phenotype) that could benefit from rosuvastatin is a novel exploration for the precise treatment. Methods The patient population for this analysis consisted of unique patients with ARDS enrolled in the SAILS trial (rosuvastatin vs. placebo). Phenotypes were derived using consensus k-means clustering applied to routinely available clinical variables within 6 hours of hospital presentation before the patients received placebo or rosuvastatin. The Kaplan–Meier statistic was used to estimate the 90-day cumulative mortality to screen for a specific population that could benefit from rosuvastatin, with a cut-off P value of <0.05. Results The derivation cohort included 585 patients with ARDS. Of the patients with the 4 derived phenotypes, those with phenotype 3 were classified as the "specific population who could benefit from rosuvastatin" since rosuvastatin resulted in a significant reduction in 90-day cumulative mortality from ARDS (hazard ratio [HR] 0.29 [95% CI 0.09, 0.93]; P=0.027). Additionally, rosuvastatin markedly improved the days free of cardiovascular failure (10.08±3.79 in the rosuvastatin group vs 7.31±4.94 in the placebo group, P=0.01) and coagulation abnormalities (13.65±1.33 vs 12.15±3.77, P=0.02) up to day 14 in the phenotype 3 cohort. Phenotype 3 was summarized as Platelethigh&Creatlow phenotype because these patients have a relatively higher platelet count (390.05±79.43×10^9/L) and lower Creat (1.42±1.08 mg/dl) than patients classified as other phenotypess. In addition, rosuvastatin seemed to increase 90-day mortality for patients classified as phenotype 4 (HR 2.76 [95% CI 0.09, 9.93], P=0.076), with an adverse effect on reducing the days free of renal failure up to day 14 (4.70±4.99 vs 10.17±4.69, P=0.01). Patients in phenotype 4 showed relatively severe illness in terms of baseline features, particularly renal failure, with high serum glucose. Therefore, phenotype 4 was defined as APACHEhigh&Serum glucosehigh phenotype. Conclusions This secondary analysis of the SAILS trial identified rosuvastatin seems to be harmful for patients classified as APACHEhigh&Serum glucosehigh phenotype, but benefit patients in Platelethigh &Creatlow phenotype, thus uncovering the novel value of rosuvastatin for the precise treatment of ARDS.